Optimization and standardization of malunggay (Moringa oleifera) seed oil refining process - Hernandez, Maria Kim C. (College of Home Economics, University of the Philippines Diliman, 2013)
Moringa oleifera seed oil was studied as a potential source of healthier oil. The sample was treated by means of water degumming and alkali refining. The refining process for malunggay was optimized and standardized using yield and free fatty acid (FFA) value as parameters.Type of refining was found to significantly (p<0.05) affect malunggay oil yield. The lowest yield, 60.2230±0.4333%, was that of oil subjected to both alkali refining and degumming. Alkali refining without degumming had an oil recovery of 77.1329±2.0488% while water degumming without alkali refining had 74.3185±1.46977%. The FFA was significantly (p<0.05) reduced in the refined oils especially the lots treated with alkali regardless of whether it was degummed or not. Alkali treated oil had an FFA of 0.1673±0.0017% which was not significantly (p>0.05) different from the oil subjected to both alkali refining and degumming with an FFA of 0.1247±0.0278%. Hence, the simpler process of alkali refining without degumming was selected for standardization. One-way analysis of variance showed that there was no significant difference in the FFA of alkali refined malunggay oil produced in three production runs. The yield in these production runs compared with the yield from the optimization phase also showed no significant difference (p>0.05) indicating a standardized process. The color of malunggay oil after refining was lighter than the unrefined oil. Using a Lovibond Tintometer, the red and yellow index decreased from 0.3r and 75y, respectively, to 0.1r and 5y in the refined oil.